Datasets for the comparison of monthly spatiotemporal precipitation and temperature changes in a predicted GeoS-NCEP/NCAR-ANN dataset - Majid Javari (Data in Brief, 2024)
This paper introduces the Precipitation and Temperature Database (PTDB), a comprehensive multi-database encompassing monthly precipitation and temperature values for about 10368 precipitation points and 65535 temperature points worldwide. The extraction of this database was facilitated by employing a large-scale GeoS-NCEP/NCAR-ANN, which operates within a global coordinate system ranging from 90°NS latitude to 180° EW longitude. The data used for this extraction was derived from a 30-year climate data set from 1991 to 2020. The PTDB is a valuable resource for conducting spatiotemporal data analysis about large-scale climate change. It is readily accessible for download through the Mendeley data platform. This distribution includes the monthly interpolated data for all 10368 precipitation points and 65535 temperature points. The geostatistical methods used in ArcGIS Pro3, along with the artificial neural network (ANN) started in MATLAB, were used to generate global monthly forecast data sets. These data sets have a resolution of 14361.49 km2 for precipitation and 2272.068 km2 for temperature. The extracted monthly raster data, converted to Excel format, can prove instrumental in climate change modeling, forecasting, and the assessment of natural hazards.